Comparison of Aetiological Risk Factors in Sporadical and Familial Epilepsies - Yaman, Mehmet; Şahin, Şevki; Yeni, Seher Naz; Karaağaç, Naci (Fırat University, 2007)
Objectives: Febril convulsion (FC) head trauma (HT) and perinatal events (PE) are the most important risk factors for epilepsy development. In this study, we aimed to show to what extent these factors contribute in sporadical and familial epilepsy. Material and Methods: Five hundred and eighty currently diagnosed epilepsy patients were followed-up for 14 months. Patients were classified as "familial epilepsy" if there is a history of epilepsy in their first or second degree relative, and as "sporadical epilepsy" if there is not. Then, a detailed anamnesis revealed the distribution of risk factors. Results: Of the total 580 patients 16.2% were familial and 83.8% were sporodical epilepsy patients. In familial epilepsy patients the rates of FC was 23.4%, HT was 4.3% and PE was 5.3%. In sporadical epilepsy patients the rates for FC, HT and PE were 8.6%, 1.6% and 2.9%, respectively. Conclusion: FC rates were found to be significantly higher in familial epilepsy. It was considered that FC in familial epilepsy is a leading sign rather than a risk factor. HT and PE rates were similar in sporadical and familial epilepsy patients. It was considered that HT and PE are not additional risk factors, particularly, in familial epilepsy, but probably they are triggering factors. ©2007, Firat University, Medical Faculty

Giriş: Febril konvulziyon (FK), kafa travması (KT) ve perinatal olaylar (PO) epilepsi gelişimi için en önemli risk faktörleridir. Bu çalışmada bu faktörlerin ne oranlarda sporadik ve ailevi epilepsi olgularının etiyolojisinde yer aldığının gösterilmesi amaçlanmıştır. Gereç ve Yöntem: Çalışma, epilepsi polikliniğinde yeni tanısı konmuş 580 hasta, 14 ay boyunca izlenerek yapılmıştır. Hastalar, birinci ve ikinci derece akrabalarından birinde epilepsi öyküsü varsa "ailevi epilepsi" yoksa "sporadik epilepsi" grubuna alınmıştır. Daha sonra detaylı anamnez sorgulaması ile bu gruplar arasında risk faktörlerinin dağılımı ortaya konmuştur. Bulgular: Toplam 580 olgunun %16.2'si ailevi epilepsi, %83.8'i sporadik epilepsi olarak sınıflandırılmıştır. Ailevi epilepsilerde FK; %23.4, KT; %4.3 ve PO; %5.3 oranında bulunmuştur. Sporadik epilepsilerde ise FK; %8.6, KT; %1.6 ve PO; %2.9 oranında saptanmıştır. Sonuç: FK ailevi epilepsilerde anlamlı düzeyde yüksek bulunmuştur. Bu durum FK'nun ailevi epilepsiler için bir risk faktöründen çok, hastalığın öncü bir bulgusu olabileceği şeklinde yorumlandı. KT ve PO ise ailevi ve sporadik epilepsi olgularında birbirine benzer oranlarda bulundu. Bu durum özellikle ailevi epilepsilerde KT ve PO'ın ek bir risk oluşturmadıklarını ve büyük olasılıkla tetikleyici faktörler olarak devreye girdiklerini düşündürmüştür. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Sporadik ve Ailevi Epilepsilerde Etiyolojik Risk Faktörü Karşılaştırması